Willingness-to-pay for the conservation of Bucari Pine Forest in Leon, Iloilo. - Anaquita, Argena Hera E.
The Bucari Pine Forest has provided the municipality of Leon in Iloilo Province with both economic and environmental benefit. However, due to the development plans, the Bucari Pine Forest has become vulnerable to degradation. This study estimated the willingness-to-pay of the residents of Leon, Iloilo for the conservation of the Bucari Pine Forest using Contingent Valuation Method. The study participants were 320- local residents from (4 upland, 4 lowland) baranbgays of Leon, Iloilo. The final data collection was conducted in January 2016 to March 2016. Seventy-five percent of the study of participants were willing to pay for the conservation of the Bucari Pine Forest. The calculated mean WTP of the study of participants with adjustment to the level of certainty was P335.00 per year of P27.92 per month. The factor that significantly affected the willingness to pay of the study participants was bid price. This means that the higher the bid price, the less likely the study participants was willing to pay for the conservation of Bucari Pine Forest. The information in this study can be used by local policy makers in dreafting conservation policies and provide awareness on the importance of the conservation of the Bucari Pine Forest.